Asynchronous Fetching and Periodic Polling for Web-Based Staffing Dashboards: Asynchronous Fetching dan Periodic Polling pada Dashboard Kepegawaian Berbasis Web - Rompas, Parabelem Tino Dolf; Saroinsong, Samuel (Indonesian Journal of Innovation Studies, 2026)
General Background: Timely information flow is a critical requirement in public administrative systems, particularly in environments with limited server infrastructure. Specific Background: At the Agricultural Modernization Implementation Center of North Sulawesi, manual staffing administration processes have caused high information latency and scheduling conflicts, motivating the adoption of a web-based staffing dashboard. Knowledge Gap: Fully real-time architectures are often resource-intensive and unsuitable for local government infrastructures, while alternative lightweight synchronization strategies remain underexplored in this context. Aims: This study aims to implement and evaluate the integration of Asynchronous Data Fetching and Client-Side Periodic Polling algorithms within a web-based staffing dashboard developed using the Rapid Application Development method. Results: Performance evaluation using Google Lighthouse recorded a Total Blocking Time of 160 ms, indicating minimal main-thread disruption, while comparative analysis showed a 99.5% reduction in information latency compared to manual procedures. Novelty: The study demonstrates a practical combination of asynchronous data loading and periodic polling as a stable and lightweight solution for administrative dashboards under server constraints. Implications: The findings indicate that government institutions with limited infrastructure can adopt similar client-side optimization strategies to achieve responsive and stable web-based administrative services without increasing server capacity. Highlights • The dashboard architecture minimizes browser main-thread workload through parallel asynchronous data loading• Periodic polling at a 15-second interval maintains stable notification synchronization under limited server resources• Administrative information latency is substantially reduced compared to conventional manual workflows Keywords Asynchronous Data Fetching; Periodic Polling; Web-Based Staffing Dashboard; Information Latency; Public Administration Systems